2020
DOI: 10.26434/chemrxiv.12122949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First Principles Study of Reactions in Alucone Growth: the Role of the Organic Precursor

Abstract: Organic-inorganic hybrid materials are a unique class of materials with properties driven by the organic and inorganic components, making them useful for flexible devices. Molecular layer deposition (MLD) offers novel pathways for the fabrication of such hybrids by using inorganic metal precursors and the vast range of organic molecules with tunable properties. To investigate and understand the mechanism of growth a combination of theoretical and experimental data is needed. In this contribution, we present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The hydroxylated Al2O3 surface terminated with one methyl group (MMA-Al2O3) that results from the adsorption of trimethylaluminium (TMA) on the Al2O3 surface was taken from our previous work with alucones. [37] We performed fundamental investigations on the interactions between the post-TMA pulse methyl-terminated Al2O3 surface and a selection of aromatic molecules with very different chemical character and these are hydroquinone (HQ), p-phenylenediamine (PD) and 4-aminophenol (AP), Figure 1. This set of aromatic molecules allows us to examine the reactivity of hydroxyl (OH) and amino (NH2) groups towards TMA as well as the preferred orientation of the organic species.…”
Section: Reactions Between Aromatic Molecules and Tma On Al2o3 Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…The hydroxylated Al2O3 surface terminated with one methyl group (MMA-Al2O3) that results from the adsorption of trimethylaluminium (TMA) on the Al2O3 surface was taken from our previous work with alucones. [37] We performed fundamental investigations on the interactions between the post-TMA pulse methyl-terminated Al2O3 surface and a selection of aromatic molecules with very different chemical character and these are hydroquinone (HQ), p-phenylenediamine (PD) and 4-aminophenol (AP), Figure 1. This set of aromatic molecules allows us to examine the reactivity of hydroxyl (OH) and amino (NH2) groups towards TMA as well as the preferred orientation of the organic species.…”
Section: Reactions Between Aromatic Molecules and Tma On Al2o3 Surfacementioning
confidence: 99%
“…It was also found that the reaction energy for TMA with NH2 or NO2 functional groups is considerably less favourable than with OH. To investigate the double reaction phenomenon for the aromatic molecules in more detail, we examine interactions of the Al2O3 surface terminated with two surface bound Al(CH3) species (2MMA-Al2O3), used in our previous work [37], with HQ, PD and AP molecules in the upright and flat lying configuration. Minimising double reactions of the organic precursor is considered an important advantage of using stiff aromatic molecules as organic precursors.…”
Section: Reactions Between Aromatic Molecules and Tma On Al2o3 Surfacementioning
confidence: 99%
See 1 more Smart Citation